Phenolic Compounds in Fruit Beverages - António Manuel Jordão (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Phenolic compounds, also called polyphenols, constitute a diverse group of secondary metabolites that exist in plants and their fruits. This important group of compounds contributes to organoleptic characteristics, such as color, taste, astringency and bitterness of fruit beverages. In addition, these compounds have gained considerable interest due to research suggesting their many health benefits especially as antioxidants. Thus, the objective of this Special Issue is to publish a compilation of original research and review papers that cover different aspects of phenolic compounds in fruit beverages, such as fruit composition, varieties and factors that could affect their phenolic composition, analytical methods for phenolic identification and quantification, impact of fruit beverages technologies on phenolics, role of phenolics in the sensorial analysis of fruit beverages and the biological activities and the health benefits of fruit beverages polyphenolics.